2009
DOI: 10.5539/ijbm.v4n5p27
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Association between Working Hour and Work Family Conflict: A Glimpse on Dhaka’s Female White Collar Professionals

Abstract: As there has been an increasing influx of white collar woman professionals in Dhaka, maintaining work-family balance is becoming more critical day by day. This study particularly attempts to explore the correlation between working hour and work family imbalance. Three FGDs, each with 10 female managers, were conducted, to make a total sample size of 30. Findings report extensive working hours, per se 9-10 hours a day, as a lethal contributor to work family conflict, whereas shorter working hours (average 5-7 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This can be substantiated by the different and myriad forms of support and assistance provided by the administration to nurture the sector. Developing countries, which includes Malaysia, will undoubtedly benefit from an unlimited women's access to microfinance; it empowers them into significantly contributing towards family income, the household's well-being and more forward changes from gender inequality (Biswas & Hassan, 2009). This is paralleled by a study by Tata & Prasad (2008), which has revealed that women micro-enterprises' performances can be affected elements like member bonding, motivation and opportunities of engaging in collaborative exchanges, appropriate training and mandatory saving.…”
Section: Introductionmentioning
confidence: 98%
“…This can be substantiated by the different and myriad forms of support and assistance provided by the administration to nurture the sector. Developing countries, which includes Malaysia, will undoubtedly benefit from an unlimited women's access to microfinance; it empowers them into significantly contributing towards family income, the household's well-being and more forward changes from gender inequality (Biswas & Hassan, 2009). This is paralleled by a study by Tata & Prasad (2008), which has revealed that women micro-enterprises' performances can be affected elements like member bonding, motivation and opportunities of engaging in collaborative exchanges, appropriate training and mandatory saving.…”
Section: Introductionmentioning
confidence: 98%
“…It is reported that spillover between work and family can be both working significantly, for example, happy family life creates enthusiasm in work life, while a problem in family life can also diminish enthusiasm and interest in work. It is imperative that today's organizations shall adequately respond to the problems of work-family conflict as it disturbs the equilibrium and thus results in a conflict between work and family lives (Theunissen et al, 2003;Alam et al, 2009). However, once the work-family conflict is noticed, the individual tries to perform in a way to maintain equal roles thereby decreasing their workfamily conflict through changing pattern and their pattern (Xu, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, once the work-family conflict is noticed, the individual tries to perform in a way to maintain equal roles thereby decreasing their workfamily conflict through changing pattern and their pattern (Xu, 2009). For organizations, its existence is detrimental as it can affect the work performance of the individual as well as overall organizational performance (Alam et al, 2009). An employee's job satisfaction, commitment, and trust in their leadership are essential for the desired performance level (Greenberg, 2005).…”
Section: Introductionmentioning
confidence: 99%